Analysing the Importance of Alps, Alp-Erens and Alp-Gazis in the Cultural Life of the Turkish World by Content Analysis - Çelebi̇can, Ümit; Avci, Muharrem; Balci, Serap (Bahattin AYDINLI, 2022)
The Turkish nation, in its 5000-year history, has established many states after the wars it waged against its enemy. From nomadic-to-nomadic life, they believed in religions such as Tengrism, Shamanism, and Islam. They have faced many droughts, famines and related migrations due to the geographical conditions. This heroic and difficult life adventure has found its place in Turkish epics in the form of anonymous products since the first periods with the oral tradition. The most important common motif of these anonymous products, which emerged both before Islam and under the influence of Islam, were characters like Alp, Alp-Eren or Alp-Gazi. This study aims to explain the Alpine type by giving examples from epics, legends and Dede Qorqut Stories, which contain epic features. This research was carried out in a scanning model, adopting a qualitative research approach. Document analysis technique was employed and the data were analysed using content analysis. Alp, which means valor, heroism, and courage, which has an important place in Turkish mythology and old Turkish life, thus being the subject of Turkish epics, and Alp-Eren or Alp-Gazi, which means dervish, mujahid, also found a place in Dede Qorqut Stories and Islamic period epics and even in local legends. In the research, it has been concluded that these motifs in question have preserved their existence in literary texts and folk culture. This study revealed that discussing and highlighting characters like Alp, Alp-Eren, and Alp-Gazi in various studies can contribute to the development of cultural and religious tourism.
Keywords: Turkish World; Epics; Legends; Dede Qorqut; Alps